Peroxisome dynamics and inter-organelle interactions in neuronal health and disease - Carmichael, Ruth E. (Frontiers in Molecular Neuroscience, 2025)
Peroxisomes are essential organelles, present in all nucleated cells, with key roles in lipid and redox homeostasis. They are important for maintaining healthy cell function, with defects in peroxisome biogenesis and/or metabolism leading to disease. Notably, patients with peroxisomal diseases exhibit predominantly neurological phenotypes, and peroxisomes are observed to be altered in a range of neurodegenerative conditions, highlighting the crucial roles they play in the brain. While most studies so far have focused on the contribution of peroxisomal metabolism, it is becoming apparent that many different aspects of peroxisome biology are necessary for healthy neural function. Peroxisomes are highly dynamic, responding to cellular needs with changes in number, shape and distribution. Furthermore, they do not act in isolation but instead interact and cooperate with a range of organelles to carry out their roles. This review summarizes our current knowledge on the importance of peroxisome dynamics and inter-organelle interactions in neuronal function and dysfunction. It considers their impact on neuronal physiology, and discusses the evidence that defects in these processes are associated with neurological pathophysiology and may thus represent a novel therapeutic target for treating diseases affecting the nervous system. Finally, the review outlines the current knowledge gaps relating to the mechanisms by which peroxisome dynamics and inter-organelle interactions influence neuronal (dys)function, proposing potential new research directions to address these and further our understanding of the multi-faceted roles peroxisomes play in brain health and disease.